1968
DOI: 10.1099/00221287-51-2-267
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bacteria and Ciliate Protozoa in the Sheep Rumen

Abstract: S U M M A R YTwo sheep were reared together and then kept on a standard diet over a period of 9 months. The rumen of one sheep contained a mixed population of ciliate protozoal species ; the other was initially unfaunated, then faunated with Entodinium caudatum and then with Entodinium and Polyplastron multivesiculatum. For each sheep diurnal and day-to-day variations in total concentration, and concentration of particular types, of bacteria, in viable counts of bacteria on non-selective and differential media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
56
4
5

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 19 publications
10
56
4
5
Order By: Relevance
“…In vivo total VFA concentration is often decreased by defaunation1-3,6). Defaunation decreases ruminal organic matter digestion and this decrease provokes a decline in total VFA production19, 21) This decrease is also explained, in part, by the disappearance of protozoal acid production. While bacterial population size is larger in defaunated rumen than in faunated rumen6,14.21-23) According to the observations of previously published reports, there was probably a larger bacterial population in defaunated rumen, although enumeration of bacteria was not done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo total VFA concentration is often decreased by defaunation1-3,6). Defaunation decreases ruminal organic matter digestion and this decrease provokes a decline in total VFA production19, 21) This decrease is also explained, in part, by the disappearance of protozoal acid production. While bacterial population size is larger in defaunated rumen than in faunated rumen6,14.21-23) According to the observations of previously published reports, there was probably a larger bacterial population in defaunated rumen, although enumeration of bacteria was not done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(Coleman, 1986). A tentative explanation of this indirect enhancement of cellulolysis is that non-cellulolytic protozoa favour the growth of cellulolytic flora by: (1) restricting the development of amylolytic flora, as a result of the ingestion of starch granules by protozoa or the selective ingestion of amylolytic bacteria, or both, (Kurihara et al 1968(Kurihara et al , 1978 and by; (2) preventing pH drop due to utilization of lactic acid (Chamberlain et al 1983) and the slow utilization of readily fermentable substrates by protozoa. These are likely to be observed in conditions where animals receive concentrate feed.…”
Section: Effect Of Defamation On Rumen Fibre Digestionmentioning
confidence: 99%
“…Warner (1966) investigated the relationship between grazing behaviour and changes in rumen microbial populations in sheep and found that the population of Oscillospira in the rumen fluctuated and the length of the trichome also changed depending upon the amount of feed consumed. Kurihara et al (1968) reported that total counts of Oscillospira in the sheep rumen tended to decrease in the presence of ciliates. Although the number of Oscillospira cells is relatively small compared with other bacterial cells, they may make a significant contribution to rumen fermentation because of their large biomass, roughly equivalent to that of ruminal ciliate protozoa (Clarke, 1979;Williams & Coleman, 1997).…”
mentioning
confidence: 99%